2017
DOI: 10.1021/acsbiomaterials.7b00615
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Aspects of Porous Biomaterials in Orthopedic Applications: A Review

Abstract: Porous biomaterials have been widely used in a variety of orthopedic applications. Porous scaffolds stimulate the cellular responses and accelerate osteogenesis. The porous structure of scaffolds, as well as their compositions, dictate cellular responses such as their adhesion, penetration, differentiation, nutrition diffusion, and bone in-growth. During the last two decades, tremendous efforts have been devoted by researchers on innovative processing technologies of porous ceramics, metals, polymers, and glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 299 publications
(629 reference statements)
0
100
0
1
Order By: Relevance
“…Interconnectivity in porous scaffolds is a crucial feature in tissue engineering and regenerative medicine. Diameters of these pores were between 15 and 80 µm, which is a suitable range for both nutrient media transportation as well as cell migration . Moreover, the role of interconnectivity in 3D scaffolds has been studied in detail and optimal pore size for vascularization was found to be 40 µm .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interconnectivity in porous scaffolds is a crucial feature in tissue engineering and regenerative medicine. Diameters of these pores were between 15 and 80 µm, which is a suitable range for both nutrient media transportation as well as cell migration . Moreover, the role of interconnectivity in 3D scaffolds has been studied in detail and optimal pore size for vascularization was found to be 40 µm .…”
Section: Resultsmentioning
confidence: 99%
“…Diameters of these pores were between 15 and 80 µm, which is a suitable range for both nutrient media transportation as well as cell migration. [32,43,44] Moreover, the role of interconnectivity in 3D scaffolds has been studied in detail and optimal pore size for vascularization was found to be 40 µm. [45,46] Somo et al [6] have found that in an in vivo trial interconnectivity with even larger pores in hydrogel tissue scaffolds allow more vascularization and blood vessel networks, 3-6 weeks after implantation.…”
Section: Resultsmentioning
confidence: 99%
“…Porous scaffold materials are a kind of materials with a 3D network structure containing a large number of voids due to their unique physical properties of large surface area, low density, and high porosity . These properties help porous scaffold materials have great application in the field of biomedicine, especially in tissue engineering .…”
Section: Introductionmentioning
confidence: 99%
“…The technique has a number of potential advantages including: the ability to tailor the porous network by controlling the processing parameters, being applicable to a number of different materials, low tooling costs and being environmentally friendly [3]. As a result it has potential applications in a number of different fields including dentistry [4] , orthopaedics [5][6][7], electrical and thermal applications [8][9][10], filtration [11] and in wound dressings [12].…”
Section: Introductionmentioning
confidence: 99%